The Relevance of the Kuttab Learning Model in Building a Generation of Noble Character - Azzahra, Naila Zalva; Anwar, Saepul; Romli, Usup (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to explore the effectiveness of the Kuttab-based learning model in shaping students' character and academic performance, as well as identify challenges and opportunities for its implementation in modern education. The method used is a literature review by collecting data from books, articles, and other relevant sources. The collected data were grouped into key themes, such as the history of Kuttab, principles of religion-based education, and the challenges and advantages of this model. Analysis was conducted to identify relevant patterns and synthesize information to support the research objectives. The results show that Kuttab education is vital in integrating religious knowledge and science, creating intellectual and spiritual balance. This model effectively shapes a generation that is intelligent and morally upright. Despite challenges like limited infrastructure and globalization, Kuttab holds significant potential for character education. The use of technology and the integration of religious curriculum with general sciences offer opportunities for developing a morally and intellectually excellent generation. Thus, Kuttab-based education can serve as a modern solution emphasizing the balance between moral values and knowledge. Keywords: Kuttab Education, integration of religion and science, character development, educational challenges, technology in education.